Innovation Types and Talent Management for Innovation - Juan A. Marin-Garcia; Lourdes E. Aznar-Mas; Fernado Gonzalez-Ladrón-de-Guevara (WPOM : Working Papers on Operations Management)
Companies need to become innovative and in order to do so, they must learn how to be able to manage the talent of their workforce In this working paper we have reviewed the literature concerning the concept of innovation as a key for the challenge for change in companies to establish a synthesis and a classification of the types of innovation required. We propose a number of competencies needed by the different staff members (support, technicians, managers, etc) as well, so that they can succeed in being innovative in different ways.